Guidelines for composing locative soundtracks - Hazzard, Adrian (2016)
This thesis investigates the composition of original adaptive musical soundtracks for locative walking activities such as cultural visiting, mobile games and urban, and nature walks; those semi-formal orchestrated walking experiences. This investigation views the ‘soundtrack’ – similarly to those typically found in ‘display’ media experiences such as films and computer games – as an accompaniment rather than the principal feature of the experience. Thus its role is to support and enhance the walking ‘narrative’. In order to best achieve this the soundtrack needs to be heard as congruent and embedded into the activity.